Light Regulation of Phytoplankton Growth in San Francisco Bay Studied Using a 3D Sediment Transport Model - Wang, Zhengui; Chai, Fei; Xue, Huijie; Wang, Xiao Hua; Zhang, Yinglong J.; Dugdale, Richard; Wilkerson, Frances (Frontiers in Marine Science, 2021)
In San Francisco Bay (SFB), light availability is largely determined by the concentration of suspended particulate matter (SPM) in the water column. SPM exhibits substantial variation with time, depth and location. To study how SPM influences light and phytoplankton growth, we coupled a sediment transport model with a hydrodynamic model and a biogeochemical model. The coupled models were used to simulate conditions for the year of 2011 with a focus on northern SFB. For comparison, two simulations were conducted with ecosystem processes driven by SPM concentrations supplied by the sediment transport model, and by applying a constant SPM concentration of 20 mg·L-1. The sediment transport model successfully reproduced the general pattern of SPM variation in northern SFB, which improved the chlorophyll-a simulation resulting from the biogeochemical model, with vertically integrated primary productivity varying greatly, from 40 g[C]·m-2·yr-1 over shoals to 160 g[C]·m-2·yr-1 in the deep channel. Primary productivity in northern SFB is influenced by euphotic zone depth ( ). Our results show that in shallow water regions (<2 m) is mainly determined by water depth, while in deep water regions is controlled by SPM concentration. As a result, has low (high) values in shallow (deep) water regions. Large (small) differences in primary productivity exist between the two simulations in deep (shallow) water regions. Furthermore, we defined a new parameter for “averaged light limitation” in the euphotic zone. The averaged chlorophyll-a concentration in the euphotic zone and share a similar distribution such that both have high (low) values in shallow (deep) water regions. Our study demonstrates that light is a critical factor in regulating the phytoplankton growth in northern SFB, and a sediment transport model improves simulation of light availability in the water column.